DISAIN ALGORITMA MODEL PREDICTIVE CONTROL (MPC) PENGENDALIAN SISTEM TATA UDARA PRESISI - Nana Sutarna (Politeknik Negeri Jakarta, 2010)
ABSTRACT The model system of precision air condition is modeled as a multivariable system with two outputs namely temperature and humidity and two inputs namely motor rotation speed and valve opening. In this model there is a problem of coupling between the input and output. Model Predictive Control (MPC) is one way to overcome the problem of coupling in multivariable systems. MPC controllers are designed without the constraints to determine a reliable algorithm. From the simulation results it appears that the controlling parameters is best horizon Hp = 10, Hu = 4, the weighting matrix R = 0.1, and Q = 3. With this parameter the output response follow the set point signal Keywords: Precision Air Systems Administration, MPC, Hp, Hu, Q and R ABSTRAK Model sistem tata udara presisi dimodelkan sebagai sebuah sistem multivariable dengan dua output yaitu temperature dan kelembaban dan dua input yaitu kecepatan putaran motor dan bukaan valve. Pada model ini ada masalah coupling diantara input dan outputnya. Model Predictive Control (MPC) adalah salah satu cara untuk mengatasi masalah coupling dalam sistem multivariable. Pengendali MPC dirancang tanpa constraints untuk menentukan agoritma yang handal. Dari hasil simulasi nampak bahwa parameter-parameter pengendali yang terbaik adalah horizon Hp=10, Hu=4, matrik pembobotan R=0.1, dan Q=3. Dengan parameter ini respon keluarannya mengikuti sinyal set point Kata Kunci : Sistem Tata Udara Presisi, MPC, Hp, Hu, Q dan R.